Investigation of the Operational Character of «Galit Wastes - Clay-Salt Slimes» System - G. G. Kruglov; N. D. Bannikov; N. N. Linkevich (Наука и техника)
The paper contains the results of experimental research. The purpose of the research is to investigate operational character of «Galit Wastes - Clay-Salt Slimes» system under various schemes of its loading. Investigations have been carried out with the help of pilot plant which models fragment of a dike and a slime storage in 1:25 scale. It has been revealed that at the initial stage of clay-salt slime loading the whole load is transferred to water. Due to this excess thrust is brought about in the soil medium. Next stages of clay-salt slime loading depend on dissipation period of excess thrust. Filling of galit wastes on clay-salt slimes leads to their strengthening in 7 - 10 days. This process is accompanied by the formation of soil layer with partial crystallization.